Survival rate and prognostic factors of Ewing Family Tumor in paediatric patients (a 11-year review) in Hospital USM from 2002-2012 - Adenam, Norhaila Mohamad (2016)
Introduction Ewing Family Tumor (EFT) is a very malignant and aggressive tumor. It was very rare tumor especially in Asia compare to western countries. During the past three decades, the prognosis of patient with EFT had improves considerably as shown in several clinical trials, mainly because of improved chemotherapy regimes. In our country, there is lack of reports in the treatment outcome and survival of children with EFT. There is no published study predicting the treatment outcome in Hospital USM at present. Objectives The objectives of this study were to evaluate the Overall Survival (OS) and Event Free Survival (EFS) rate of patients who were diagnosed with EFT. We want to evaluate the demographic data and identify the possible predictive factors that determine the EFS and OS rate of those children with EFT and treated in Hospital USM. Methodology This is a retrospective record review of children aged 0-18 years with EFT. Children were identified from registration data in Oncology Unit and medical records from Record Office HUSM. In case of uncontactable or deceased patients, a letter was sent to State Registry to obtain the end result/outcome of the patients. The associations of demographic and clinical factors with patients outcome were determined by Cox regression. Survival curves were estimated by the Kaplan-Meier method and compared by the Log-rank test. Results There were 51 patients identified from the registration but then only 29 children were enrolled in this study, which full filled all the inclusion criteria. The mean duration follow up was 21 months. The OS rate at 1, 2, 3 and 5 years were 62.1%, 44.8%, 30.2% and 21.6% respectively. The EFS rate at 1, 2, 3 and 5 years were 41.9%, 26.7%, 17.8% and 0% respectively. Multivariate Cox regression analysis showed that presence of surgical intervention (p=0.030) and major complications (p=0.045) were significant prognostic factors to the survival of EFT in this study. Conclusion Survival rate among our patients was comparable to other developing countries. However we are far away if compared to developed countries as the survival rate only achieved almost half from their survival rate. We are able to identify two significant independent prognostic factors to the survival for EFT in our patients which were surgical intervention and presence of major complications.